2016
DOI: 10.1093/mutage/gew026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genotoxicity and cytotoxicity of filling pastes used for pulp therapy on deciduous teeth using the micronucleus test on bone marrow from mice (Mus musculus)

Abstract: Pulp therapy is the last resort for preserving deciduous teeth. However, the genotoxic and cytotoxic effects of many products used in this therapy are not well established. The aim of this study was to use the micronucleus test on bone marrow from mice to evaluate the genotoxic and cytotoxic effects of four filling pastes: zinc oxide, calcium hydroxide P.A., mineral trioxide aggregate and an iodoform paste (iodoform + camphorated + paramonochlorophenol + rifamycin + prednisolone). Male Swiss mice were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Concerning the potential of products containing zinc oxide or iodoform pastes, there is a scarcity of studies, especially those with the comet methodology. Pires et al [19] showed that comet assay revealed that iodoform paste did not damage DNA either Guedes Pinto paste, but Santos et al [12] found genotoxic potential, translated as a higher frequency of micronuclei.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the potential of products containing zinc oxide or iodoform pastes, there is a scarcity of studies, especially those with the comet methodology. Pires et al [19] showed that comet assay revealed that iodoform paste did not damage DNA either Guedes Pinto paste, but Santos et al [12] found genotoxic potential, translated as a higher frequency of micronuclei.…”
Section: Introductionmentioning
confidence: 99%
“…To deciduous pulp therapy, the paste must be resorbable, provide radiopacity, not interfere with the successor tooth germ's development, and be biocompatible with periapical tissue [1,[3][4][5]. Additionally, it is expected that an ideal filling material does not induce genotoxic and/or cytotoxic effects, but also there's also no consensus on such effects in the studies [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, the root canal filling material should be biocompatible, antibacterial, stable, and easy to operate in order to avoid any complication involved during or after operation . Numerous materials, such as zinc oxide‐eugenol cement, iodoform paste, and calcium hydroxide, have been used as root canal filling materials. However, they cannot meet all the above requirements.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, zinc oxide‐eugenol cement is lack of antibacterial activity . The biocompatibility of iodoform paste still needs improvement . Calcium hydroxide, which is one of the most commonly used capping materials, frequently presents disadvantages such as the low hardness and dissolution that will result in a loose filling .…”
Section: Introductionmentioning
confidence: 99%